PELAKSANAAN PELAYANAN KESEHATAN DI PUSKESMAS PANIPAHAN KECAMATAN PASIR LIMAU KAPAS KABUPATEN ROKAN HILIR DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 25 TAHUN 2009 TENTANG PELAYANAN PUBLIK - Fit Andriyani; Mexsasai Indra; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This research aims to describe the implementation of health services at thePanipahan Health Center, Pasir Limau Kapas District, Rokan Hilir Regency andto determine the implementation of Good Governance at the Panipahan HealthCenter, Pasir Limau Kapas District, Rokan Hilir Regency. This research isempirical or sociological legal research. The research location is in thePanipahan District, Pasir Limau Kapas District, Rokan Hilir Regency, namely thePanipahan Community Health Center. Based on research conducted, the resultsshow that health services at the Panipahan Community Health Center are carriedout based on Regional Government and Central Government Regulations andPolicies. The implementation of health services at the Community Health Centerconsists of services from the Individual Health Unit and the Community HealthUnit. The programs at the Community Health Center are KIA, Nutrition, HealthPromotion, Environmental Health and other programs. The flow of healthservices and service standards at the Panipahan Community Health Center havebeen adjusted to the services provided to the community to improve the level ofpublic health. Supporting factors in the implementation of health services at thePanipahan Community Health Center consist of organization, policy andmanagement. Meanwhile, the inhibiting factors are the implementation of healthservices at the Panipahan Community Health Center, namely human resources,infrastructure and funds/budget. The efforts made by the Rokan downstreamdistrict health service to improve services at the Panipahan Community HealthCenter are recruiting human resources and competency training for existinghuman resources, prioritizing development of facilities and infrastructure as wellas appropriate budget allocation.Keywords: Panipahan Community Health Center, Public Services, HealthServices.